2015
DOI: 10.1159/000430470
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab in Daily Clinical Practice for Age-Related Macular Degeneration: Treatment of Exudative Age-Related Macular Degeneration in Real Life

Abstract: Purpose: To describe the anatomical and functional outcomes in patients with exudative age-related macular degeneration (AMD) undergoing ranibizumab therapy in real-life practice. Methods: This is a retrospective analysis of patients with exudative AMD treated with ranibizumab. Visual acuity (VA) and optic coherence tomography characteristics at baseline and at the end of the follow-up, clinical forms of the disease, delay between diagnosis and treatment as well as the number of follow-up visits and of intravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…We observed that patients with the lowest baseline VA also had the most pronounced gain in VA, a finding described previously by others (Cazet‐Supervielle et al. ; Gillies et al. ).…”
Section: Discussionsupporting
confidence: 90%
“…We observed that patients with the lowest baseline VA also had the most pronounced gain in VA, a finding described previously by others (Cazet‐Supervielle et al. ; Gillies et al. ).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have been conducted in this important topic and the terminology for anti-VEGF treatment response has been defined in detail. 15,16,25 The response to anti-VEGF agents has been categorized either as functional or morphological response. 15 Amoaku et al 15 have recently proposed to classify patients with nAMD into four categories with regard to their functional response based on the change in VA, which were as follows, good responders (45 ETDRS letter gain from the baseline), suboptimal responders (gain of 0-5 letters from Figure 3 The simultaneous fluorescein and indocyanine green angiography images of a 71-year-old female retinal angiomatous proliferation patient.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,26 Factors affecting drug pharmacodynamics and pharmacokinetics such as receptor downregulation, autoantibody formation, change in drug distribution, and absorption have also been shown to be related to nonresponse. 15,25,26 Suboptimal treatment of the patients with less frequent treatment regimens is another important clinical factor which can affect the treatment success and underlie nonresponse. Real-life studies showed that many of the patients were undertreated especially in the PRN treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ranibizumab, one trial showed that only 6% of subjects typically require monthly dosing, while the remainder can be treated less frequently using an individualized approach [10] . Thus, real-life treatment of nAMD is typically individualized for most subjects following initial monthly treatment [11][12][13] , with clear benefits seen with early treatment [14] . Indeed, individualized dosing is recommended in the prescribing information for ranibizumab and the intervals between doses can be extended according to the treating physician's opinion and an assessment of disease severity [11] .…”
Section: Introductionmentioning
confidence: 99%